2020
DOI: 10.3389/fgene.2020.560186
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Colorectal Cancer-Related MicroRNA-mRNA Regulatory Network by Microarray and Bioinformatics

Abstract: Colorectal cancer (CRC) is one of the most malignant cancers with high morbidity and mortality. MicroRNAs (miRNAs) are small non-coding RNAs that affect biological processes by binding to mRNAs and regulating their expression, and epigenetic alterations including miRNA dysregulation are significantly involved in CRC development. Determining the effect of the miRNA-mRNA network on CRC could be helpful for developing novel therapeutic targets and prognostic biomarkers, and even improving survival. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The study thus provides a glimpse of possible effects that can be mediated by GPR15 in colon cancer beyond its classical function as a T-cell trafficking protein. Another study on mRNA and miRNA signatures in human COAD patient samples also reported reduced GPR15 expression in tumors and potential miRNA mediated regulation of GPR15 levels in COAD 40 .…”
Section: Discussionmentioning
confidence: 88%
“…The study thus provides a glimpse of possible effects that can be mediated by GPR15 in colon cancer beyond its classical function as a T-cell trafficking protein. Another study on mRNA and miRNA signatures in human COAD patient samples also reported reduced GPR15 expression in tumors and potential miRNA mediated regulation of GPR15 levels in COAD 40 .…”
Section: Discussionmentioning
confidence: 88%
“…In cancer investigations, PNOC was related to high inflammatory status and oxidative stress in C6 glioma cells, which also was highly up-regulated in pediatric brainstem ganglioglioma tissues and epithelial ovarian cancer, and in analysis of high-risk gastrointestinal stromal tumor, PNOC was reported as a prognostic biomarker ( 45 48 ). In a study of mRNA and microRNA network in colorectal cancer, PNOC and its targeting microRNAs were also prognostic markers for evaluation of patients ( 49 ). In our analysis, PNOC was up-regulated in cholangiocarcinoma samples, though the difference didn’t achieve significance.…”
Section: Discussionmentioning
confidence: 99%
“…First, we used a relaxed cutoff threshold (adjusted p < 0.25), which could include more false positives compared to a stricter cutoff. In contrast, it is well known that a small sample size generally yields higher adjusted p -values [ 83 , 84 , 85 , 86 ]. However, the results of downstream functional analyses and data from previous publications further confirmed the validity of our methodology and findings.…”
Section: Discussionmentioning
confidence: 99%